Analysis of Learning Evaluation in Kindergarten Pertiwi 2 Penambongan with Kirkpatrick Model - Rahayu, Imaniah Kusuma; Arifiani , Anggi Desy; Istikhori, Muhammad (Universitas Negeri Semarang, 2025)
Early childhood education is a very basic stage so it is necessary to provide various activities that can develop various aspects of development including cognitive, language, social, emotional, physical, and motoric (Anderson, 1993). Pertiwi 2 Penambongan kindergarten has various excellent programs, including: character & morals education, loose part learning, outing class, peak topic activities. Character and morals education through the habit of reading and reciting Qur’an, congregational Dhuha prayer, memorizing doa & hadiths, daily prayers, Asmaul Husna, and Arabic language introduction. The aim of this research is evaluating the quality of learning implementation at Pertiwi 2 Penambongan Kindergarten with Kirkpatrick Model. The respondents were teachers, students, and parents. Data were collected using quetionnaires, interview, observation, and documentation. Data analysis with quantitative descriptive analysis. The result obtained are 1) students' reactions showed that the implementation of learning in Pertiwi 2 Penambongan Kindergarten was in very good criteria with a percentage of 83.7%. 2) student learning in very good criteria with a percentage of 88.15% 3) the behavior of students shows in very good criteria with a percentage of 81.15%. 4) the result of the implementation of learning in Pertiwi 2 Penambongan Kindergarten on sufficient criteria with a percentage of 68.8%. As a conclusion, the implementation of learning in Pertiwi 2 Penambongan Kindergarten is very good, but learning outcomes are influenced by several factors. One of them is family factors. Therefore, synergy between teachers and parents is needed so that the education that has been implemented at school can be maximized.